Fabrication of a PAN–PA6/PANI membrane using dual spinneret electrospinning followed by in situ polymerization for separation of oil-in-water emulsions. (29th July 2020) - Faraji, Mehdi; Nabavi, Seyed Reza; Salimi-Kenari, Hamed
Abstract : A polyacrylonitrile–polyamide 6/polyaniline (PAN–PA6/PANI) doped membrane was prepared using dual spinneret simultaneous electrospinning of PAN and PA6 and in situ polymerization of aniline at low temperature. Abstract : A polyacrylonitrile–polyamide 6/polyaniline (PAN–PA6/PANI) doped membrane was prepared using dual spinneret simultaneous electrospinning of PAN and PA6 and in situ polymerization of aniline at low temperature. The performance of the membrane was investigated in separation of non-surfactant and different surfactant oil/water emulsions like SDS, Tween 80 and Span 80. The field emission electron microscopy (FESEM) and energy dispersive X-ray (EDS) results revealed that PAN–PA6 nanofibers are coated uniformly with PANI. According to the atomic force microscopy (AFM) maps, the surface roughness of the fabricated membrane was increased from 51 to 83 after coating, which can improve the membrane flux and oil rejection. The stress–strain test displayed that PA6 improved the PAN mat tensile strength from 3.88 to 11.86 MPa. Post treatment of PAN–PA6/PANI with doping in HCl 1 M can improve the membrane hydrophilicity and separation efficiency. The effect of the polymerization time on the membrane porosity and pore volume was investigated. The optimum time of polymerization where the membrane has high permeate flux (326 Lmh) and oil rejection (97.8%) was found to be 60 min for non-surfactant (hexane/water) emulsion separation. The performance of the membrane was studied for separation of petroleum ether, gasoline and gas oil emulsions in water. The reusability and chemical resistance of the membrane in harsh conditions were investigated.